Gratitude and Happines of New Student After Covid-19 Pandemic - Nabillah Saputri; Ade Irma Oktiyani; Ambar Nurdian Syaputri; Sandro Saragi (CV. Doki Course and Training, 2024)
Gratitude in man is often associated with the feeling of happiness in his heart. Happy human is a self-sufficient and meaningful individual. The goal of this research is to establish a link between gratitude and the joy of new student Raden Fatah State Islamic University after the covid-19 pandemic. The study uses a quantitative method of correlation, with the number of responders of 29 people, the scale used is cg-6 (all gratitude nare scale). His Pearson's effect is 1,000 ** and its significance between its two variability is 0,000, which means there is a strong link between gratitude and happiness in new university, raden fatah state islamic university. It is thus inferred that there is a strong connection between gratitude and happiness in humans.